Colective elementary excitations of bose-einstein condensed two-dimensional magnetoexcitons strongly interacting with electrom-hole plasma - Moscalenco, Sveatoslav (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2005)
The collective elementary excitations of a system of Bose-Einstein condensed two-